SALES EFFECT OF DIGITAL MARKETING IN SMALL AND MEDIUM-SIZED ACCOMMODATION ENTERPRISES IN CORE CAPPADOCIA - Erdoğan, Yakup; Güneren Özdemir, Ebru (Dergi Karadeniz, 2021)
The subject of the study is the effects on sales of the use of digital marketing tools by tourism SMEs in the Core Cappadocia region. The data obtained for the purpose of determining the uses and impacts were obtained as a result of the questionnaire applied to the owners or managers in 48 accommodation enterprises, which have been defined as SME in the Core Cappadocia region. The collected data were analysed with SPSS 21 package program. It has been determined that there is a positive significant relationship between the usage of digital marketing tools and their effects on sales, and there is no significant change in the annual turnover of the enterprises after the use of digital marketing tools. In addition, it has been determined that the use of digital marketing tools does not differ significantly according to the availability of a marketing department.
Keywords: Çekirdek Kapadokya; Dijital pazarlama; Turizm (Diğer); Digital marketing; Tourism (Other); Digital Marketing; Sales Effect of Digital Marketing; Small and Medium-Sized Accommodation Enterprises; Core Cappadocia; Core Cappadocia; цифровой маркетинг; влияние цифрового маркетинга на продажи; гостиничный бизнес малого и среднего бизнеса; Core Cappadocia.; Satış etkisi; Dijital Pazarlama; Dijital Pazarlamanın Satış Etkisi; Küçük ve Orta Ölçekli Konaklama İşletmeleri; Çekirdek Kapadokya; Sales effect; 8. Economic growth